Indonesia Rejoining OPEC: Dynamics of the Oil Importer and Exporter Countries - Badaruddin, Muhammad (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2015)
Reactivation of Indonesia’s full membership to the Organization of the Petroleum Exporting Countries (OPEC) triggered discussion surrounding global petroleum governance. The country which decided to suspend its full membership at the end of 2008, currently labelled as net oil importer. However, in OPEC terms Indonesia never really left, instead of the organization termed it as a